PENGARUH PERSEDIAAN BARANG DAGANG DAN KETEPATAN WAKTU PENEGIRIMAN PADA CV. ALLEGRA NUSANTARA - Fadilla, Nur; Sari, Syahriah (Journal of Business Administration (JBA), 2024)
This Research aims to determine,: 1) customer perceptions of the inventory of goods at CV. Allegra Nusantara 2) Customer perception of the timeliness of delivery at CV. Allegra Nusantara 3) Customer perception of sales volume at CV. Allegra Nusantara. 4) The effect of inventory of goods on sales volume 5) Effect of Timeliness on Sales Volume at CV. Allegra Nusantara 6) Effect of inventory of goods and timeliness of delivery at CV. Allegra Nusantara. This study uses a quantitative approach with questionnaire data collection methods and interviews. The sample in this study amounted to 80 respondents taken from 406 population with the proposive sampling method and the slovin formula. Data analysis was carried out by multiple linear regression analysis using SPSS Version 16.